The Effect of a Simulated Commercial Flight Environment with Hypoxia and Low Humidity on Clotting, Platelet, and Endothelial Function in Participants with Type 2 Diabetes – A Cross-over Study - Konya, Judit; Spurgeon, Benjamin E. J.; Al Qaissi, Ahmed; Sathyapalan, Thozhukat; Ajjan, Ramzi; Madden, Leigh; Naseem, Khalid M.; Garrett, Andrew Thomas; Kilpatrick, Eric; Atkin, Stephen L. (Frontiers in Endocrinology, 2018)
Aims: To determine if clotting, platelet and endothelial function were affected by simulated short haul commercial air flight conditions (SF) in participants with type 2 diabetes (T2DM) compared to controls. Methods: 10 participants with T2DM (7 females, 3 males) and 10 controls (3 females, 7 males) completed the study. Participants were randomized to either spend 2 hours in an environmental chamber at sea level conditions (temperature: 23oC, oxygen concentration 21%, humidity 45%), or subject to a simulated 2-hour simulated flight (SF: temperature: 23oC, oxygen concentration 15%, humidity 15%), and crossed over 7 days later. Main outcome measures: clot formation and clot lysis parameters, functional platelet activation markers and endothelial function measured by reactive hyperaemia index (RHI) by EndoPAT and serum microparticles. Results: Comparing baseline with simulated flight conditions, clot maximal absorption was increased in controls (0.375±0.05 v 0.39±0.05, p<0.05) and participants with T2DM (0.378±0.089 v 0.397±0.089, p<0.01), whilst increased basal platelet activation for both fibrinogen binding and P-selectin expression (p<0.05) was seen in participants with T2DM. Parameters of clot formation and clot lysis, stimulated platelet function (stimulated platelet response to ADP and sensitivity to prostacyclin) and endothelial function were unchanged. Conclusion: Whilst SF resulted in the potential of denser clot formation with enhanced basal platelet activation in T2DM, the dynamic clotting, platelet and endothelial markers were not affected, suggesting that short haul commercial flying adds no additional hazard for venous thromboembolism for participants with T2DM compared to controls. Key words: type 2 diabetes, hypoxia, flight simulation, platelet function, endothelial function, clotting